2000
DOI: 10.1007/s002100000307
|View full text |Cite
|
Sign up to set email alerts
|

[ 3 H]ac-RYYRWK-NH 2 , a novel specific radioligand for the nociceptin/orphanin FQ receptor

Abstract: The hexapeptide ac-RYYRWK-NH2 has been described as a potent partial agonist at the nociceptin (NC)/orphanin FQ receptor which has no affinity for mu-, kappa- or delta-opioid receptors. However, it is not clear whether ac-RYYRWK-NH2 is truly selective for the NC receptor, and ac-RYYRWK-NH2 has therefore been radiolabelled and characterised in receptor-binding experiments. Saturation experiments with [3H]ac-RYYRWK-NH2 binding to rat cortical membranes revealed a single high affinity site for [3H]ac-RYYRWK-NH2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Structure activity studies were performed by using the Ac-RYYR-I/W-K-NH 2 sequence as a template. The binding affinity was decreased by the head-to-tail cyclization of Ac-RYYRWK-NH 2 [17] and increased by N-terminal acylation with a pentanoyl group [18] or the replacement of the Tyr 2,3 residues with (pF)Phe [19] . A NOP receptor agonist was generated by N-terminal alkylation of the central core YYRW with groups bearing a guanidine function [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Structure activity studies were performed by using the Ac-RYYR-I/W-K-NH 2 sequence as a template. The binding affinity was decreased by the head-to-tail cyclization of Ac-RYYRWK-NH 2 [17] and increased by N-terminal acylation with a pentanoyl group [18] or the replacement of the Tyr 2,3 residues with (pF)Phe [19] . A NOP receptor agonist was generated by N-terminal alkylation of the central core YYRW with groups bearing a guanidine function [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Cyclic analogues of 3 like cyclo-(-RYYRWK-) had only a scarce affinity. 59 A SAR study on 4 showed that the removal of acetyl or Ala substitution of Arg1, Tyr2, or Tyr3 almost suppressed affinity, whereas this effect was much smaller for the same substitution of one of the other three residues or the removal of Lys6. Moreover, the removal of the terminal amide group had almost no effect.…”
Section: Other Peptidesmentioning
confidence: 98%
“…53 Whereas the introduction of helix structure in 1 is generally favorable to activity, a conformational constraint to a b-strain diminishes both affinity and activity, as in Other compounds derived from 1, which also showed an increased activity due to conformational restraints, are some cyclic analogues, such as the agonists cyclo 59 (see Table XII for cyclopeptides and Table IX for some acyclic counterparts). Another ligand derived from N/OFQ is retronociceptin methyl ester, with poor affinity in vitro (IC 50 5 480 mM) but active on mice by i.c.v.…”
Section: Nociceptin Receptor (Nop) Agonists and Antagonists K 615mentioning
confidence: 98%
See 1 more Smart Citation
“…21 Also potent cyclic analogues may provide information on possible biologically active conformations of the peptide. Only a limited number of cyclic analogues of N/OFQ have been reported to date, [22][23][24][25] and these have all involved cyclization via a disulfide bond; cyclo[Cys 10 ,Cys 14 ]N/OFQ(1-14)NH 2 23,24…”
mentioning
confidence: 99%